Επαλήθευση απλοποιημένων μοντέλων Michaelis-Menten - Πατσατζής, Δημήτριος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2017)
The intracellular Michaelis-Menten mechanism is one of the most simple and most popular mechanisms in the field of systems biology. Its kinetics is also widely employed in enzymology, pharmacokinetics and ecology. The dynamics of the mechanism has been the subject of an extensive research effort and a large bibliography is currently available. In this work the MM mechanism is analysed with the Computational Singular Perturbation (CSP) method, which is the algorithmic counterpart of geometric asymptotic analysis. CSP is employed for the derivation of new reduced models and the validation of the existing ones, which were derived on the basis of Quasi Steady- State (QSSA) and Partial Equilibrium Approximations (PEA). The main purpose of this work is to establish the validity of (i) the CSP-generated reduced models, by examining their stability and accuracy and (ii) the QSSA and PEA-generated reduced models, by considering the conditions in which CSP simplifies to PEA and QSSA. This work aims to provide robust reduced models, which are valid in large domains of the parameter space.